Nesting doctoral students in collaborative North-South partnerships for health systems research - Svetla Loukanova; Helen Prytherch; Antje Blank; Els Duysburgh; Göran Tomson; Lars L. Gustafsson; Ali Sié; John Williams; Melkizedeck Leshabari; Walter E. Haefeli; Rainer Sauerborn; Sharon Fonn (Taylor & Francis Group, 2014)
Background: The European Union (EU) supports North-South Partnerships and collaborative research projects through its Framework Programmes and Horizon 2020. There is limited research on how such projects can be harnessed to provide a structured platform for doctoral level studies as a way of strengthening health system research capacity in sub-Saharan Africa (SSA). Objective: The aim of this study was to explore the challenges of, and facilitating factors for, 'nesting' doctoral students in North-South collaborative research projects. The term nesting refers to the embedding of the processes of recruiting, supervising, and coordinating doctoral students in the overall research plan and processes. Design: This cross-sectional qualitative study was undertaken by the EU-funded QUALMAT Project. A questionnaire was implemented with doctoral students, supervisors, and country principal investigators (PIs), and content analysis was undertaken. Results: Completed questionnaires were received from nine doctoral students, six supervisors, and three country PIs (86% responses rate). The doctoral students from SSA described high expectations about the input they would receive (administrative support, equipment, training, supervision). This contrasted with the expectations of the supervisors for proactivity and self-management on the part of the students. The rationale for candidate selection, and understandings of the purpose of the doctoral students in the project were areas of considerable divergence. There were some challenges associated with the use of the country PIs as co-supervisors. Doctoral student progress was at times impeded by delays in the release of funding instalments from the EU. The paper provides a checklist of essential requirements and a set of recommendations for effective nesting of doctoral students in joint North-South projects. Conclusion: There are considerable challenges to the effective nesting of doctoral students within major collaborative research projects. However, ways can be found to overcome them. The nesting process ultimately helped the institutions involved in this example to take better advantage of the opportunities that collaborative projects offer to foster North-South partnerships as a contribution to the strengthening of local research capacity.